2018
DOI: 10.4314/ijbcs.v11i5.21
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of latex harvesting technologies on agronomic and physiological parameters and profitability of some rapid metabolic class clones of rubber tree (<i>Hevea brasiliensis</i>) in southwestern Côte d’Ivoire

Abstract: Rubber tree rapid-metabolism clones generally have interesting agronomic and physiological characteristics. However, they are mostly sensitive to tapping panel dryness and breakage due to wind. This could be probably due to overexploitation caused by high tapping frequencies and/or high hormonal stimulation systems. To try solving this problem, a study was carried out over nine years using clones PB 260, PB 280 and PB 330 planted at a density of 510 plants/ha in southwestern Côte d'Ivoire. The experimental des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This approach is adopted in response to increasing labour costs and skilled-tapper shortage. Although some studies showed that quick starter clones have a low response to ethylene stimulation and consequently are less suitable to the low-frequency tapping (Atsin et al 2014;Atsin et al 2017), some new quick-starter clones may be more responsive to ethylene application. On the other hand, several studies showed that high sugar loading clones were able to amplify the benefit of low-frequency tapping (Gohet et al 1996;Soumahin et al 2009;Lacote et al 2010;Diarrassouba et al 2012).…”
Section: Limited Use Of Latex Diagnosis In Breeding Programmentioning
confidence: 99%
“…This approach is adopted in response to increasing labour costs and skilled-tapper shortage. Although some studies showed that quick starter clones have a low response to ethylene stimulation and consequently are less suitable to the low-frequency tapping (Atsin et al 2014;Atsin et al 2017), some new quick-starter clones may be more responsive to ethylene application. On the other hand, several studies showed that high sugar loading clones were able to amplify the benefit of low-frequency tapping (Gohet et al 1996;Soumahin et al 2009;Lacote et al 2010;Diarrassouba et al 2012).…”
Section: Limited Use Of Latex Diagnosis In Breeding Programmentioning
confidence: 99%